2022
DOI: 10.46843/jiecr.v3i2.68
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning LKPD Development Based On Learning Using Nearpod Applications For Integrated Learning In Elementary School

Abstract: This study aims to describe the validity, practicality, and an effectiveness of LKPD with the theme of growth and development of living things using the Blended Learning model in integrated thematic learning in grade III elementary school.This research is included in research and development (Research and Development) with the ADDIE model. Collecting data using observations, questionnaires, written tests and interviews and then analyzed quantitatively and qualitatively.This research produces a teaching materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…The research outcomes were consistent with the previous study conducted by Fimala et al (2022), which showed an improvement of 86 percent in the students' learning results from the pre-test and post-test score data after employing a blended learning student worksheet using the Nearpod application in class. Ahmed and Elmubark (2022) conducted a study that demonstrated a significant difference in the mean scores of the pre-test and post-test, and the students participating in the study were delighted with the application of the Nearpod as an interactive media in the reading teaching-learning process.…”
Section: Discussionsupporting
confidence: 89%
“…The research outcomes were consistent with the previous study conducted by Fimala et al (2022), which showed an improvement of 86 percent in the students' learning results from the pre-test and post-test score data after employing a blended learning student worksheet using the Nearpod application in class. Ahmed and Elmubark (2022) conducted a study that demonstrated a significant difference in the mean scores of the pre-test and post-test, and the students participating in the study were delighted with the application of the Nearpod as an interactive media in the reading teaching-learning process.…”
Section: Discussionsupporting
confidence: 89%
“…Adanya media pembelajaran pada proses belajar mengajar disekolah haruslah diterapkan. Upaya ini sangatlah baik untuk merangsang meningkatkan keterampilan menyimak peserta didik dalam mengikuti proses pembelajaran, serta meningkatkan motivasi peserta didik untuk lebih dalam menggali tentang materi yang disampaikan sehingga tujuan dan pencapaian guru menjadi suskses, (Fimala et al, 2022). Selain itu peserta didik juga dapat memecahkan permasalahn dengan mudah dikarena adanya media pembelajaran yang memudahkan peserta didik memahami materi sehingga peserta didik merasa dihadapkan dengan pristiwa yang nyata.…”
Section: Pembahasan Analisis Penggunaan Video Animasi Untuk Meningkat...unclassified
“…The analysis involves a nuanced examination of how each phase of ADDIE is implemented within the context of thematic learning. The meticulous scrutiny of data through observation, interviews, and documentation facilitates a deeper understanding of the dynamics at play (Desyandri et al, 2021;Fimala et al, 2022;Mukmin & Primasatya, 2020;Suzana et al, 2021;Wahyuni & Ananda, 2021).…”
Section: Introductionmentioning
confidence: 99%